The Effect of Living Values Education Program (LVEP)-Based Sex Education Animation Videos on the Pancasila Profile of Elementary Students - An-Nisa Apriani; Laila Rahmawati; Muchammad Ilham Rahmat Ramadhan; Emiliana; Serli Nur Cahyati; Siti Nur Hidayah (Jurnal Ilmiah Sekolah Dasar, 2025)
Sex education plays a crucial role in fostering students’ understanding of gender, personal boundaries, and reproductive health, yet its implementation at the elementary level often remains limited due to the lack of appropriate and engaging instructional media. This condition highlights the need for innovative learning resources that are both pedagogically sound and value-oriented. This study aims to examine the effect of Living Values Education Program (LVEP)-based sex education animation videos on the development of the Pancasila Student Profile among elementary school students. The study employed a quasi-experimental method using a pretest–posttest control group design. The research population consisted of elementary school students, with samples selected through cluster random sampling involving students from grades II to VI, divided into experimental and control groups. The experimental group received instruction using LVEP-based sex education animation videos, while the control group was taught using static image media. Data were collected through structured observations, interviews, and questionnaires designed to assess indicators of the Pancasila Student Profile before, during, and after the intervention. The collected data were analyzed using a t-test at a significance level of 0.05. The findings indicate that the use of LVEP-based sex education animation videos has a statistically significant effect on enhancing students’ Pancasila Student Profile. These results suggest that value-based animated instructional media can serve as an effective pedagogical approach to support character education and holistic student development in elementary education.